Estimation of wood cover in a semi arid african landscape by breakdown of the spectral response of SPOT HRV XS: application to the north of Burkina Faso - (:unkn) unknown (My University, 1998)
Breakdown of the spectral response approach has been applied to the assessment of wood cover in a semi arid eastern African landscape. The spectral response to a SPOT HRV XS image was modified on the basis of signature and of relative abundance of four elementary parts (foliage, associated shadow and two types of naked ground). Postulating special relationships between wood cover and type of soil rendered possible the analysis. The relationship between wood cover and the associated shadow is explained through geometrical model of LI and Strahler, whose parameters were evaluated from on-site data. The assessment obtained from the relative abundance of the cover was highly correlated to an independent assessment established on the basis of big scale pictures taken from a plane. This approach is able to provide coherent assessment of the wood cover, even in condition of heterogeneous soil.
Keywords: African Research